2020
DOI: 10.3390/ijerph17155304
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Utilization of Medical and Dental Services among Homeless People in South Korea

Abstract: (1) Background: Homelessness contributes to both needs for care and barriers to access. This study aimed to explore the utilization of medical or dental services using Andersen’s model for a vulnerable population of homeless in South Korea. (2) Methods: The data were applied from the first national survey for homeless people in South Korea, 2016. Totally 2032 persons participated in the interview survey. This study team requested the raw data through the public portal and analyzed them. (3) Results: The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The process of study selection is shown in Figure 1 (flow chart [ 21 ]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and 31 studies investigating adults [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The process of study selection is shown in Figure 1 (flow chart [ 21 ]). In sum, n = 41 studies were included in our final synthesis (ten studies investigating children/adolescents [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and 31 studies investigating adults [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). We will present an overview of included studies by age group (children/adolescents; adults) in the next two sections.…”
Section: Resultsmentioning
confidence: 99%
“…Data came from Europe ( n = 4 studies; Germany, n = 2; Sweden, n = 1; Finland, n = 1), South America ( n = 6 studies, all studies were from Brazil), North America ( n = 13 studies; United States, n = 12; Canada, n = 1), Asia ( n = 6 studies; China, n = 2; South Korea, n = 1; Thailand, n = 1; Israel, n = 1; Sri Lanka, n = 1), Africa ( n = 2 studies; Burkina Faso, n = 1; Sudan, n = 1). Three [ 32 , 39 , 48 ] out of the 31 studies had a longitudinal design, whereas the other 28 studies had a cross-sectional design [ 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations